Ryanodine‐receptor inhibition by dantrolene effectively suppresses ventricular arrhythmias in an ex vivo model of long‐QT syndrome. (22nd January 2018) - Frommeyer, Gerrit; Krawczyk, Julius; Ellermann, Christian; Bögeholz, Nils; Kochhäuser, Simon; Dechering, Dirk G.; Fehr, Michael; Eckardt, Lars
Abstract: Aims: A significant antiarrhythmic potential of ryanodine receptor inhibition was reported in experimental studies. The aim of the present study was to assess potential antiarrhythmic effects of dantrolene in an experimental whole‐heart model of drug‐induced long‐QT syndrome (LQTS). Methods: In 12 isolated rabbit hearts, long‐QT‐2‐syndrome was simulated by infusion of erythromycin (300 μM). Twelve rabbit hearts were treated with veratridine (0.5 μM) to mimic long‐QT‐3‐syndrome. Results: Monophasic action potentials and ECG showed a significant prolongation of QT‐interval (+71 ms, P < 0.01) and action potential duration (APD, +43 ms, P < 0.01) after infusion of erythromycin as compared with baseline. Similar results were obtained in veratridine‐treated hearts (QT‐interval: +43 ms, P < 0.01; APD: +36 ms, P < 0.01). Both erythromycin (+36 ms, P < 0.05) and veratridine (+38 ms) significantly increased dispersion of repolarization. Additional infusion of dantrolene (20 μM) did not significantly alter QT‐interval and APD but resulted in a significant reduction of dispersion of repolarization (erythromycin group: –33 ms, P < 0.05; veratridine group: –29 ms, P < 0.05). Lowering of potassium concentration resulted in the occurrence of early afterdepolarizations (EAD) and polymorphic ventricular tachycardia (VT) in 9 of 12 erythromycin‐treated hearts (175 episodes) and 8 of 12 veratridine‐treated hearts (66 episodes). Additional infusion of dantrolene significantly reduced occurrence of polymorphic VT and resulted in occurrence of EAD and polymorphic VT in 1 of 12 erythromycin‐treated hearts (18 episodes) and 1 of 12 veratridine‐treated hearts (3 episodes). Conclusion: Inhibition of the ryanodine receptor by dantrolene significantly reduced occurrence of polymorphic VT in drug‐induced LQTS. A significant reduction of spatial dispersion of repolarization represents a major antiarrhythmic mechanism. These results imply that dantrolene may represent a promising antiarrhythmic option in drug‐induced LQTS.